2013
DOI: 10.1007/s00464-013-3162-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparotomy for small-bowel obstruction: first choice or last resort for adhesiolysis? A laparoscopic approach for small-bowel obstruction reduces 30-day complications

Abstract: Laparoscopic adhesiolysis requires a specific skill set and may not be appropriate in all patients. Notwithstanding this, the laparoscopic approach demonstrates a benefit in 30-day morbidity and mortality even after controlling for preoperative patient characteristics. Given these findings in more than 9,000 patients and consistent rates of SBO requiring surgical intervention in the United States, increasing the use of laparoscopy could be a feasible way of to decrease costs and improving outcomes in this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 21 publications
3
48
0
9
Order By: Relevance
“…1,22,23 Since the first report of Bastug et al for successful laparoscopic adhesiolysis in 1991, 9 technological developments and increased experience with LS have led to a number of studies reporting advantages of LS, including a shorter postoperative hospital stay, fewer complications, and less postoperative pain. [10][11][12][13][14][15][16][17] Kim et al reported significant reductions in return of bowel function (4.3 vs. 6.6 days, p=0.02), and hospital stay (8.1 vs. 15.2 days, p=0.04). 17 Moreover, in a systematic review comparing laparoscopic adhesiolysis with open adhesiolysis for SBO treatment, LS resulted in reduced risks of morbidity, mortality, and surgical site infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,22,23 Since the first report of Bastug et al for successful laparoscopic adhesiolysis in 1991, 9 technological developments and increased experience with LS have led to a number of studies reporting advantages of LS, including a shorter postoperative hospital stay, fewer complications, and less postoperative pain. [10][11][12][13][14][15][16][17] Kim et al reported significant reductions in return of bowel function (4.3 vs. 6.6 days, p=0.02), and hospital stay (8.1 vs. 15.2 days, p=0.04). 17 Moreover, in a systematic review comparing laparoscopic adhesiolysis with open adhesiolysis for SBO treatment, LS resulted in reduced risks of morbidity, mortality, and surgical site infection.…”
Section: Discussionmentioning
confidence: 98%
“…9 Since then, with the recent technical advances and increased experience in LS, many previous studies have shown the safety, feasibility, and potential superiority of a laparoscopic approach for the treatment of SBO. [10][11][12][13][14][15][16][17] Moreover, some studies have reported long-term outcomes, such as the frequency and management of recurrence after LS. [18][19][20] Despite many studies have been reported on safety of laparoscopic adhesiolysis in SBO, prospective randomized trials comparing LS and OS in the treatment of SBO have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic peritoneal lavage has proven to be an effective emergent treatment for perforated diverticulitis with a low conversion and high efficacy rate [23][24][25]. Furthermore, Ming-Zhe et al showed that laparoscopic adhesiolysis for small bowel obstruction was not inferior with respect to the number of iatrogenic enterotomies, surgical site infection, pulmonary complications, or overall mortality, and this has been supported by numerous studies [26][27][28][29]. Finally, two important randomized studies, albeit with small populations, have shown the non-inferiority of laparoscopic management of perforated gastroduodenal ulcer disease [30,31].…”
Section: Hospital Bed Sizementioning
confidence: 64%
“…Given these findings in more than 9000 patients and consistent rates of ASBO requiring surgical intervention in the United States, increasing the use of laparoscopy could be a feasible way to decrease costs and improve outcomes in this population [49].…”
Section: Laparoscopymentioning
confidence: 97%